Pharmacotherapy of Trigeminal Neuralgia - Luangmonkong, Theerut (Journal of Basic and Applied Pharmacology, 2015)
Trigeminal Neuralgia (TN) is a type of disease which main symptom is the facial pain. Although, the disease pathogenesis remains unclear, the abnormality of trigeminal nerve which functions as the sensory and motor neuron of the face is supposed to be the cause. At the abnormal site, the voltage-gated sodium channels are in the hyperactive state, and this hyperactivation causes the rapid and frequent pain. From the proposed mechanism of abnormality, carbamazepine, a voltage-gated sodium channels inactivators, is the first-line agent for the management of trigeminal neuralgia because it has the mechanism of action that directly relates with the disease pathogenesis. The studies of carbamazepine use in the treatment of trigeminal neuralgia also proved the benefit. However, before starting carbamazepine use, patients should be advised to determine the HLA-B*1502 gene in order to decrease the risk of severe skin adverse reactions. Other drugs used in the studies of trigeminal neuralgia management are oxcarbazepine, anticonvulsants, and muscle relaxants.